The Emergence of Holographic Perspective Towards a Convergence of Scientific and Religious World views - Vadaya D, Thomas (Journal of Dharma, 1987)
This study presents the holographic perspective of the world as proposed by David Bohm and the holographic model of the Brain as proposed by Karl Pribram. It also points out some of the similarities between this emerging world view in science and that held by eastern religions. The hologram is one of the truly remarkable inventions of modern physics. It is a kind of three-dimensional "picture" producedby holography or what is known in common parlance as lensless photography. Holography is a way of recording and then reconstructing waves. The waves may be of any kind, light, sound, or X-ray. The word "holography" originates from the Greek word "holos", meaning "the whole". By using this word, the inventor of holography wanted to stress that it records complete information about a wave-both its amplitude and its phase. In conventional photography only the distribu- tion of the amplitude is recorded in a two-dimensional projection of an object onto the plane of the photograph. A hologram, on the contrary, regenerates not a two-dimensional image of an object, but the field of the wave which it scatters.The physical foundation of holography is the science of waves, their interference and refraction. The purest kind or' light available to us is pro- duced by a laser, which sends out a beam in which all the waves are of one frequency. When two laser beams touch they produce an interference pattern of light and dark waves that can be recorded 011 a photographic plate. If one of the beams, intead of coming directly from the laser, is first reflected off an object such as a human face, the resulting record will be a hologram of the face.